The mediating effects of motivation on the relations between occupational stress and physical activity among underresourced afterschool program staff - Anqi Deng; Nicole Zarrett; Allison M. Sweeney (BMC, 2024)
Abstract Objective Guided by Self-Determination Theory, this study aimed to examine the potential mediating effects of autonomous and controlled motivations on physical activity (PA) experiences of afterschool program (ASP) staff with occupational stress. Method A total of 58 ASP staff provided full data. Staff occupational stress and self-determination motivations for PA were assessed. Participants' daily moderate-to-vigorous physical activity (MVPA) was measured using accelerometer wear. A path analysis was used to address the research purpose. Results Occupational stress negatively and indirectly predicted daily MVPA which was mediated by controlled motivation (β = − 4.15, p <.05). Autonomous motivation directly and positively predicted daily MVPA across all types and levels of ASP staff occupational stress (β = 9.93, p =.01). Conclusions Autonomous motivation is a powerful predictor of staff PA levels despite the degree to which they experience stress. In contrast, controlled motivations are more vulnerable to occupational stress, and can lead to lower MVPA. Trial registration Connect Through PLAY: A Staff-based Physical Activity Intervention for Middle School Youth (Connect). https://clinicaltrials.gov/ct2/show/NCT03732144 . Registered 11/06/2018. Registration number: NCT03732144.